TỔNG QUÁT VỀ ĐẶC TÍNH HÓA LUỒNG LƯU LƯỢNG IP - Anh, Dương Tuấn; Minh, Hoàng (Vietnam Journal of Science and Technology, 2012)
DIFFERENT OBSERVATIONS OVER CHARACTERIZATION OF IP TRAFFIC FLOWS In a distributed environment with multiple form applications and a limited system resources the question of ensuring quality of services (QoS) from service providers (SP) to users becomes a more difficult task. With respect to the mentioned question, network operators and administrators have to understand the system dynamics through measuring IP traffic for characterizing patterns of IP traffic flows so that the ranking services can be set up for priority control strategy. Starting from actual needs, a research topics entitled "An IP traffic flows characterization" has been being carried out with the aim of establishing a system of constrained conditions on the basics of each IP traffic characteristics. The system of constrained conditions would be exploited for network security and information surveillance, quality of services (QoS) assurance as well. In this paper, a report in two paraghaphs is made on different important observations over characteristics of Internet traffic flows, excepting a brief introduction on scope of the work in the first paragraph and discussions on further research in the fourth one. In the second paragraph, a brief on the characterization of IP traffic flows is reviewed from internet providers viewpoint. In the third one, important characteristics of different IP trafics in scattering medium are sketched out from the QoS assurance point of view. Different suggestions for carrying out further research from the point of network security, and information surveillance are discussed in the fourth paragraph. With respect to these points, it is important to address that a multi-dimensional characterizing IP traffic flows is required to be adopted.